Perfil epidemiológico da hanseníase em crianças e adolescentes menores de 15 anos em Fortaleza - CE - Guilhon, Rose Mary Porto (2023)
Leprosy is an ancestral, chronic and infectious disease that has become a public health problem because it causes deformities and disabilities, compromising society. This theme is relevant because of the detection of cases in people under 15 years of age and because it indicates the existence of active and recent transmission, showing the difficulty in controlling the disease. The objective was to know the clinical and epidemiological aspects in children under 15 years old with leprosy, in Fortaleza - Ceará, from 2010 to 2019, through a descriptive, cross-sectional, historical study, with a quantitative approach. Of the 380 notified cases, 60.3% were male, 68.9% in the age group of 10 to 14 years and 51.8% of brown color/race. The paucibacillary operational forms (60.8%), with single lesion (47.6%) and negative smear microscopy (56.3%), predominated over the multibacillary forms (39.2%), and the tuberculoid (36.8%) and dimorphic (30.5%) clinical forms were seen more frequently. Among those evaluated, 11.6% had disabilities at diagnosis and 7.4% at discharge. The degree of physical disability 1 (52.4%) and 2 (65.0%) predominated in the dimorphic clinical form. Of the 380 participants, 318 (83.7%) had information related to reactions and of these, 65.6% had no reactions, 15.8% had type 1 reaction, 1.1% type 2 and 1.3% type 1 and 2. As for the mode of entry, 92.4% of the cases were new cases and 64.2% were detected by referrals. 81.3% were discharged for cure and 6.3% abandoned the treatment. We crossed the variables and found statistically significant associations between gender and education (p = 0.011), disabilities and reaction episodes (p = 0.000) and, smear microscopy and age group (p = 0.003). This is a relevant study because, besides describing the leprosy situation, it may contribute to the planning of control measures and to decision making.